MANAJEMEN PERALATAN PROTEKSI RADIASI: ANALISIS KETERSEDIAAN DAN KESESUAIAN ALAT PELINDUNG DIRI DI INSTALASI RADIOLOGI RUMAH SAKIT X - Angella, Shelly; Yulistio , Muhammad Pratama (Journal of Hospital Administration and Management (JHAM), 2023)
Radiation exposure in radiology installations poses high risks to staff and patients. To mitigate this, the use of Personal Protective Equipment (PPE) according to regulations, such as PERBAPETEN No. 4 Year 2020, is mandatory, including aprons, thyroid shields, Pb gloves, and Pb glasses. This study analyzed the availability and suitability of radiation protection PPE in the Radiology Installation of X Hospital based on PERBAPETEN No. 4 Year 2020 and Minister of Health Decree No. 1250 Year 2009. Using a Descriptive Comparative mixed-methods design, data were collected through observation (checklist sheets) and interviews at the Radiology Installation of X Hospital (April-June 2022). Results showed that PPE availability was incomplete; aprons and thyroid shields were 100% available and compliant with standards (apron 100% of 7 elements, thyroid shield 100% of 4 elements). However, Pb gloves and Pb glasses were unavailable, though they were in the procurement process. This incompleteness indicates a procurement management gap. Recommendations include expediting the procurement of missing PPE and regular monitoring and evaluation to optimize radiation risk management and standard compliance.